2021
DOI: 10.1063/5.0064685
|View full text |Cite
|
Sign up to set email alerts
|

Assessing and rationalizing the performance of Hessian update schemes for reaction path Hamiltonian rate calculations

Abstract: The reaction path Hamiltonian (RPH) can be used to calculate chemical reaction rate constants, going beyond transition-state theory in taking account of recrossing by providing an approximation to the dynamic transmission coefficient. However, the RPH necessitates the calculation of the Hessian matrix at a number of points along the minimum energy path; the associated computational cost stands as a bottleneck in RPH calculations, especially if one is interested in using high-accuracy electronic structure metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Correcting for such effects demands evaluation of α­( T ); this is in itself a computationally expensive exercise, requiring thermal averaging of a number of MD trajectories (typically on an ab initio PES or reactive force-field model) initiated at the TS in order to evaluate the flux-side correlation function. To address this inefficiency, we have recently shown how α­( T ) can be accurately and efficiently approximated using a reaction-path Hamiltonian (RPH) model parametrized using information available from standard NEB optimization of the MEP; importantly, we have also demonstrated that RPH construction can be further accelerated by using a variety of Hessian propagation schemes, thereby avoiding expensive ab initio Hessian calculations for a dense set of intermediate images. , As shown in Figure for the example reaction of molecular hydrogen association at the cobalt center in HCo­(CO) 3 , relatively simple Hessian update schemes combined with MD simulations using the RPH model enable accurate approximation of α­( T ), even for reactions in which recrossing is quite significant. Such methods demonstrate how one can improve on the treatment of TST rate theory in a simple computational scheme; although we note that the challenge of accurately modeling the underlying PES remains.…”
Section: Challenges To Reaction-discovery Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Correcting for such effects demands evaluation of α­( T ); this is in itself a computationally expensive exercise, requiring thermal averaging of a number of MD trajectories (typically on an ab initio PES or reactive force-field model) initiated at the TS in order to evaluate the flux-side correlation function. To address this inefficiency, we have recently shown how α­( T ) can be accurately and efficiently approximated using a reaction-path Hamiltonian (RPH) model parametrized using information available from standard NEB optimization of the MEP; importantly, we have also demonstrated that RPH construction can be further accelerated by using a variety of Hessian propagation schemes, thereby avoiding expensive ab initio Hessian calculations for a dense set of intermediate images. , As shown in Figure for the example reaction of molecular hydrogen association at the cobalt center in HCo­(CO) 3 , relatively simple Hessian update schemes combined with MD simulations using the RPH model enable accurate approximation of α­( T ), even for reactions in which recrossing is quite significant. Such methods demonstrate how one can improve on the treatment of TST rate theory in a simple computational scheme; although we note that the challenge of accurately modeling the underlying PES remains.…”
Section: Challenges To Reaction-discovery Simulationsmentioning
confidence: 99%
“…(a) MEP for the insertion of molecular hydrogen H 2 at the cobalt center of HCo­(CO) 3 , the active catalytic species in the Heck–Breslow hydroformylation previously studied by ARD simulations. (b) Calculated flux-side correlation functions given by a standard RPH simulation (requiring multiple Hessian matrix evaluations along the MEP) and by our recent work in which Hessian propagation schemes (in this case, Powell–symmetric–Broyden [PSB]) are used to build the RPH …”
Section: Challenges To Reaction-discovery Simulationsmentioning
confidence: 99%
See 1 more Smart Citation